The Association between PM2.5 Exposure and Hippocampal Volume: A Systematic Review - Lukito, Elizabeth Feloni; Tandarto, Kevin; Stella, Maureen Miracle; Ivan, Ignatius; Sudharta, Harvey; Golahi, Gilbert; Sutanto, Kenny Wijaya; Turana, Yuda; Santi, Bryany Titi; Budiman, Yanto; et al. (Asian Pacific Journal of Environment and Cancer, 2022)
Background: Existing air quality is decreasing, as evidenced by the increase in air pollution. Air pollution does not only affect the respiratory system, but also affecting the nervous system, and furthermore causing impaired cognitive function that can be predicted through the image of the hippocampus. Objective: This study wanted to determine the significance of the relationship between PM2.5 (Particulate Matter) pollutant exposure and hippocampal volume in adults. Method: This research is a PRISMA 2020 based systematic study using Google Scholar, PubMed, and Proquest as databases. Research inclusion criteria were studies with subjects over 19 years old, using MRI techniques, published in English, having sufficient data for extraction. Result: There are 5 studies from 2015 to 2020 which stated that there was no statistically significant relationship between PM2.5 pollutant exposure and hippocampal volume (n = 5) (P-value > 0.05, 0.71, 0.8, 0.32), and the study obtained significant results (n = 1) (P-value < 0.005). Discussion: Although the results of the study did not prove a significant difference in hippocampal volume, several recent theories regarding hippocampal neurogenesis in adults are able to support these results. Conclusion: From this study, it was not proven that there was a significant relationship between PM2.5 pollutant exposure and hippocampal volume.